Assistance in Digital Technology Based Audio Visual Media Production for the Preservation and Promotion of Rumah Gadang Salo Payakumbuh - Muhammad Sayuti; MelisaSuardi MelisaSuardi; Tedy Wiraseptya; Aggy Pramana Gusman; Harkamsyah Andrianof; Okta Andrica Putra; Abulwafa Muhammad (Journal of Community Service and Application of Science, 2026)
Rumah Gadang Salo Payakumbuh is one of the Minangkabau cultural heritage sites with significant historical, philosophical, and architectural values. However, the utilization of digital media as a means of cultural documentation, education, and promotion remains limited, resulting in insufficient dissemination of its cultural values to the wider community. This community service program aimed to assist local partners in producing audiovisual media based on digital technology as an effort to preserve and promote Rumah Gadang Salo Payakumbuh. The implementation methods included field observation, partner needs assessment, creative concept development, audiovisual production training, video shooting assistance, video editing, and joint evaluation with the partners. The program integrated the expertise of the Visual Communication Design discipline in visual communication planning, cinematography, and video editing with the Computer Science discipline in multimedia technology and digital media utilization to produce informative, engaging, and accessible digital content. The primary output of this program was a cultural documentary video that serves as a medium for education, cultural tourism promotion, and digital documentation of local cultural heritage. The results indicate that the partners improved their knowledge and technical skills in audiovisual media production while obtaining a promotional medium capable of expanding public access to information about Rumah Gadang Salo through various digital platforms. This community service activity is expected to support technology-based cultural preservation, enhance community participation in safeguarding cultural heritage, and strengthen the sustainable promotion of cultural tourism destinations in Payakumbuh City.